PENGARUH INSENTIF, KOMITMEN TUGAS DAN TANGGUNG JAWAB TUGAS TERHADAP KINERJA ANGGOTA POLDA PADA BAGIAN LALULINTAS BPKB POLDA KEPULAUAN RIAU - Rona Tanjung; Zalmadri Putra (Postgraduate Management Journal, 2021)
The regression coefficient is significant or the Work Incentive variable has an effect on performance. The regression coefficient is significant or the Task Commitment variable has an effect on the performance variable. The regression coefficient is significant or the variable of the Work Responsibilities of Members in the Traffic Section of the Riau Islands Police BPKB has an effect on the performance variable. The Anova test produces an F count of 11.014> F table 2.82 with a significance level (probability number) of 0.05. F count> F table then Ho is rejected and hipothesys is accepted. Then the regression coefficient of Work Incentives, Work Commitment and Responsibilities together has a significant effect on the Member Performance variable.